Echocardiographic assessment of functional changes of prosthetic valve after transcatheter aortic valve implantation in one year follow up: insights from the multicenter, randomized DIRECT trial. (25th November 2020) - Toutouzas, K; Karmpalioti, M; Benetos, G; Drakopoulou, M; Xanthopoulou, M; Stathogiannis, K; Latsios, G; Synetos, A; Bei, E; Voudris, V; Kosmas, E; Mastrokostopoulos, A; et al.
Abstract: Introduction: The DIRECT trial (Predilatation in Transcatheter Aortic Valve Implantation (TAVI) Trial) was a multicenter, randomized, clinical trial designed to evaluate the safety and efficacy of TAVI with or without balloon aortic valvuloplasty (BAV) in patients with symptomatic, severe aortic valve stenosis. Purpose: To investigate by echocardiography the functional changes of self-expanding prosthetic valves during the first year after TAVI with or without BAV. Methods: One hundred seventy one consecutive patients with severe aortic stenosis were enrolled at 4 centers and randomized to TAVI using self-expanding prostheses with (pre-BAV) or without pre-dilatation (no-BAV). Transthoracic echocardiography was obtained at baseline, 30 days and 1 year after TAVI. Results: Of 171 patients, 86 patients were randomized to pre-BAV group and 85 to no-BAV group. Over the one year, 7 (4%) patients died and in 18 (10%) there was no available paired 30 day/1 year echo. At baseline echocardiography the peak and mean aortic valve gradient and the aortic valve area (AVA) in no-BAV group were 77.31±22.56 mmHg, 47.23±14.98 mmHg and 0.69±0.16cm 2 and in pre-BAV group 81.97±23.17 mmHg, 49.39±14.78 mmHg and 0.65±0.15cm 2 respectively. One year after TAVI, patients in no-BAV and pre-BAV group showed stable peak and mean aortic valve gradients similar to those at 30 days (from 16.36±7.88 to 14.51±6.6 mmHg vs. 17.17±8.88 to 15.95±9.97 mmHg and from 8.87±4.23 to 7.99±4.04 mmHg vs. 9.39±4.79 to 8.38±5.02 mmHg respectively, P<0.001 vs. baseline). The AVA was similarly stable in one year follow up in no-BAV group (from 1.85±0.43cm 2 to 1.85±0.44cm 2, P<0.001 vs. baseline) and in pre-BAV group (from 1.86±0.49cm 2 to 1.84±0.39cm 2, P<0.001 vs. baseline). The incidence of moderate or severe paravalvular regurgitation remained unchanged in both groups (from 4.7% to 5.7% in no-BAV group and from 5.8% to 6.6% in pre-BAV group). Conclusions: In both pre-BAV and no-BAV groups the improvement in hemodynamics of self-expanding prosthetic valves remained durable during the one year echocardiographic follow up assessment. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): MEDTRONIC